Pengaruh Advertising Dan Special Event Terhadap Peningkatan Brand Awareness - Anwar, Rima Rahmani; Anggraini T., Rosita (Jayapangus Press, 2021)
The right communication to grow brand awareness can be realized through advertising. In addition, events are one of the strategies to have a positive influence in communicating a brand. This study wants finding out how building and increasing brand awareness through advertising on social media Instagram and the